EVALUASI PENERAPAN PSAK NO.109 TENTANG PELAPORAN KEUANGAN AKUNTANSI ZAKAT, INFAQ/SHADAQAH PADA BAZNAS KOTA YOGYAKARTA - Yuli Chomsatu Samrotun, Amita Vani Budiarti, Endang Masitoh & (Universitas Slamet Riyadi, 2017)
Bond Accountant Indonesia has issued financial accounting standardsregarding financial report of religious obligatory, infaq/shadaqah. This researchwas conducted on BAZNAS Yogyakarta city which is one of the Agency's amil zakat.This research aims to know the application of financial reporting in the BAZNAS cityof Yogyakarta PSAK No. 109 accounting of religious obligatory, infaq/shadaqah.The population in this research is the financial reporting accounting zakat andinfaq/shadaqah on BAZNAS Yogyakarta city. The sample in this research is datafinancial reporting accounting zakat and infaq/shadaqah on BAZNAS Yogyakartacity by 2015. Methods of analysis used in this study is the method used is theinteractive analysis. In this method, there are three main components, namely datareduction (1) (2) the representation of the data (3) conclusions. The result of theresearch was the city BAZNAS, writing financial reports are still not fully inaccordance with PSAK NO. 109.Keywords: financial reports, PSAK NO. 109